Competitividade nos contextos urbano e do new public governance: um estudo em organiza????es e entidades do esporte em munic??pios - Shintani, Cristina Emy (2014)
Environmental changes influence the activities of various organizations since the advent of labour specialization. Since then competitiveness studies multiply in different literature areas as economy, management, sport and public administration to solve the survival problem and success of organizations involved in different sectors and contexts. This scenario projects into the daily actions and quality of life of different city residents and so is possible to observe the importance of sport to the physiological and social wellness of the individuals and cities, due the power to generate business opportunities in local, regional and international levels. Considering the governmental duty to guarantee necessary infrastructure and service for the cities competitiveness, and the importance of the local public administration and governance to do so, this work tries to identify how the competitiveness elements observed in the context of the new public governance approach in the local sport context may contribute for the sport activity in the municipality. With this goal in mind, an exploratory descriptive research of the competitiveness phenomenon will be held, by the use of a qualitative multiple case analysis involving different interest groups with sport activity in S??o Bernardo do Campo and S??o Caetano do Sul cities, located in S??o Paulo???s metropolitan area. This work aims to contribute to the local sport activities and to achieve elements for the development of the sport management in Brazil.